Risk Disclosure Level and Its Relationship with Profitability: A Study of Annual Reports of Companies in the Transportation Sector - Almira Yumna Putri; Achmad Hizazi; Ratih Kusumastuti (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2026)
This study examines the relationship between risk disclosure levels and profitability in transportation companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The transportation industry is characterized by high exposure to operational, financial, regulatory, and market-related risks, which necessitates transparent and comprehensive communication regarding potential threats to business sustainability and long-term performance. Using a quantitative correlational approach, this study measures the level of risk disclosure through systematic content analysis of companies’ annual reports, while profitability is evaluated using the Return on Assets (ROA) indicator. The analysis is conducted to identify the extent to which transparent risk reporting contributes to improved financial outcomes. The findings indicate a significant positive relationship between risk disclosure and profitability, suggesting that companies providing more comprehensive and detailed risk information tend to achieve higher financial performance. Furthermore, the results demonstrate that transparency plays a crucial role in enhancing investor confidence, strengthening corporate governance, and supporting sustainable business practices, particularly in high-risk sectors such as transportation.